Parisian Theologians in the 1330s - Courtenay, William J. 1935- (2019)
In recent decades the publication of additional documentary sources and doctrinal and prosopographical studies for the University of Paris in the 1330s has radically expanded our information about theologians in what was once an obscure decade. Using a variety of evidence, this article outlines what we now know about bachelors of the Sentences active at Paris in the 1330s, part of what the author once called "the dormition of Paris."
Keywords: 1330s; Sentences; University of Paris; Theology